Improving Speaking Skills Through Project Based Learning in Indonesian Language Subjects for Class V. B Students at SD Negeri 151/IV, Jambi City - Oktavia, Gessy Frischa; Nazurty, Nazurty; Sastrawati, Eka (Journal of Innovation and Research in Primary Education, 2025)
Speaking skills are one of the essential competencies in Indonesian language learning at elementary schools. However, initial observations in class V.B at SD Negeri 151/IV Jambi City showed that most students still experienced difficulties in expressing ideas orally, characterized by lack of confidence and limited vocabulary usage. This study aims to improve the speaking skills of Grade V.B students of SD Negeri 151/IV Jambi City by implementing the Project-Based Learning (PjBL) model combined with the Show and Tell method. Speaking skills are an important aspect in language learning that reflect students' ability to express ideas coherently and confidently. This research involved 25 fifth-grade students and was conducted over two cycles using the Classroom Action Research (CAR) method. Data collection techniques included observation, testing, and documentation. The study results showed that before the intervention, students' speaking skills were still low, marked by a soft voice, limited vocabulary, and anxiety when speaking in public. After the implementation of PjBL and Show and Tell, there was a significant increase in confidence, fluency, and the organization of ideas when speaking. In Cycle I, the class average score increased from 69 (pre-action) to 76, and in Cycle II it rose further to 83. The percentage of students meeting the minimum competency increased from 32% in the pre-action stage to 84% in Cycle I, and reached 92% in Cycle II. The application of this combined method had a positive impact on students' speaking skills by encouraging active participation, critical thinking, and collaboration. Therefore, the integration of Project-Based Learning and Show and Tell is recommended as an effective instructional strategy for enhancing speaking skills in elementary school students.